Udział prokuratora w procesie cywilnym w okresie stalinizmu (1945–1956) - Błaszczak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article deals with the participation of the prosecutor in the civil trial during the Stalinist period. The article analyzes the various forms of participation of the prosecutor with special attention to his procedural position. The article also addresses the rationale for the prosecutor’s participation and the consequences associated with it. As a result of the changes introduced in 1950, the institution of the prosecutor gained new powers, which were introduced into the Code of Civil Procedure. The study also refers to the influence of Soviet law on Polish law and the expansion of the scope of the prosecutor’s activity at the level of litigation.
Keywords: prokurator; proces cywilny; totalitaryzm; powództwo; współuczestnictwo; socjalizm; interes publiczny